PERILAKU REMAJA TERHADAP PENCEGAHAN HIV/AIDS DI SMK TERPADU BINA INSAN SUMEDANG - Khodijah, Upus Piatun; Mega Nurrahmawati (Jurnal Kebidanan Besurek, 2024)
The level of knowledge and awareness on the prevention of HIV / AIDS is lacking especially among teenagers. Indonesian health demographics survey results show the number of young people in Indonesia reached 30% of the total population of approximately 1.2 million inhabitants. From the amount of data contained in West Java, there are as many as 1904 the number of cases of HIV and AIDS affected as many as 494 cases. This study aims to determine the behavior of teenager in High School Departement Terpadu Bina Insan Subdistricts Paseh Underdistrict Sumedang. This type of research is descriptive research. The sample in this study were all male and female students High School Departement Terpadu Bina Insan Subdistricts Paseh Underdistrict Sumedang is 69 respondents. Using the technique of total sampling. Analysis of the data using univariate analysis. From the results of the study concluded that the behavior in prevention HIV/AIDS in teenager High School Departement Terpadu Bina Insan resulting lack of knowledge , negative attitudes and actions wrong. Suggestions in this research that health workers in order to further increase focus on the prevention of transmission of HIV / AIDS, especially among teenagers. And as a teacher you should add learning materials on HIV / AIDS so that its students can add knowledge about the prevention of HIV / AIDS.